2015
DOI: 10.1002/jmri.24928
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantification and mapping of anomalous pulmonary venous flow with four‐dimensional phase‐contrast MRI and interactive streamline rendering

Abstract: Background Cardiac MRI is routinely performed for quantification of shunt flow in patients with anomalous pulmonary veins, but can be technically-challenging to perform. Four-dimensional phase-contrast (4D-PC) MRI has potential to simplify this exam. We sought to determine whether 4D-PC may be a viable clinical alternative to conventional 2D phase-contrast MR imaging. Methods With institutional review board approval and HIPAA-compliance, we retrospectively identified all patients with anomalous pulmonary vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…The use of sparse reconstructions has also been explored for improving 4D flow or phase contrast imaging 111 , to evaluate valvular insufficiency, improve accuracy in delineating shunt pathology, assess anomalous flow in pulmonary veins, and visualize hemodynamics in congenital heart disease 112116 . Sparse reconstructions have been used to obtain single breath-hold characterization of portal flow 117 and can yield improved vessel conspicuity while retaining accuracy of quantification of portal flow 118 .…”
Section: Clinical Applications Of Sparse Reconstruction Techniquesmentioning
confidence: 99%
“…The use of sparse reconstructions has also been explored for improving 4D flow or phase contrast imaging 111 , to evaluate valvular insufficiency, improve accuracy in delineating shunt pathology, assess anomalous flow in pulmonary veins, and visualize hemodynamics in congenital heart disease 112116 . Sparse reconstructions have been used to obtain single breath-hold characterization of portal flow 117 and can yield improved vessel conspicuity while retaining accuracy of quantification of portal flow 118 .…”
Section: Clinical Applications Of Sparse Reconstruction Techniquesmentioning
confidence: 99%
“…4D flow CMR allows for comprehensive post-hoc evaluation of blood flow patterns by 3D blood flow visualization and quantification of flow parameters [ 18 ]. Previous studies have shown that quantification of ventricular volume and function can be accomplished with 4D flow MRI with precision and inter-observer agreement comparable to that of SSFP cine imaging [ 19 , 20 ]. Strain analysis would be a valuable additional feature of 4D flow CMR, as this would allow for integrative analysis of flow and function in one sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration techniques based on compressed sensing (CS) − often combined with non-Cartesian sampling, with and without exploitation of spatio-temporal correlations − have also been applied to 4D flow CMR achieving similar acceleration rates [1215]. One major disadvantage of most proposed CS techniques is their relatively long off-line reconstruction time, reportedly being in the range of 45 to 60 min [12, 13, 16].…”
Section: Introductionmentioning
confidence: 99%